Tooth glaze composition, tooth glaze and application

By adding clay minerals and diatomaceous earth as inorganic additives to the enamel composition, combining alcohols and ester solvents to control the refractive index difference, the problem of mismatch in optical properties of dental restoration materials is solved, and a clear and bright enamel effect is achieved, which improves the aesthetics and texture of the teeth.

CN120381412APending Publication Date: 2025-07-29AIDITE (QINHUANGDAO) TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510523542.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-04-24
Publication Date
2025-07-29

AI Technical Summary

Technical Problem

The existing dental restoration materials are difficult to match natural teeth in optical properties, resulting in whitening and affecting aesthetics in the repaired teeth. The optical uniformity of the existing enamel layer is poor, making it impossible to present the clear and bright effect of natural teeth.

Method used

The tooth enamel composition containing glass powder and dispersion composition is used. By adding clay minerals and/or diatomaceous earth to the composition as inorganic additives, combining alcohols and ester solvents, the refractive index difference between the glass powder and the dispersion composition is controlled within 0.1, adjust the refractive and scattering of light, and improve the uniform stability and transparency of the composition.

Benefits of technology

It significantly improves the transparency and uniformity of the tooth glaze surface, ensures that the glaze surface has a transparent and clear texture close to natural teeth, and improves the aesthetic effect and overall quality of oral restoration.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120381412A_ABST
    Figure CN120381412A_ABST
Patent Text Reader

Abstract

The invention provides a tooth glaze surface composition, a tooth glaze surface and application, the tooth glaze surface composition comprises glass powder and a dispersion composition, and the dispersion composition comprises an organic liquid and an inorganic auxiliary agent; wherein the absolute value of the difference value between the refractive index of the glass powder and the refractive index of the dispersion composition is within 0.1; the organic liquid comprises a combination of an alcohol solvent and an ester solvent, and the inorganic auxiliary agent comprises clay mineral and / or diatomite. According to the present invention, the dispersion stability of the tooth glaze surface composition can be significantly improved, the layering condition of the tooth glaze surface can be avoided, the alcohol solvent and the ester solvent are adopted as the organic liquid, and the transparency of the organic liquid is adjusted so as to effectively adjust the refractive index of the dispersion composition, such that the difference between the refractive index of the dispersion composition and the refractive index of the glass powder is small; after the two components are mixed, the light refraction and scattering phenomena at an interface are greatly reduced, and the finally prepared clear glaze can present transparent and clear texture closer to that of natural teeth.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of dental restorative materials, and particularly to an enamel composition, an enamel surface, and applications thereof. Background Art

[0002] Among dental restorative materials, ceramic materials have attracted much attention due to their excellent aesthetics, biocompatibility, and good mechanical properties. Because they can highly simulate the color and texture of natural teeth, bringing a more natural and beautiful restoration effect to patients, they occupy an important position in restorative applications such as dental crowns and veneers.

[0003] In addition, as patients' aesthetic standards continue to rise, a restoration matrix with a single color is difficult to meet the needs in clinical application scenarios. By precisely adjusting the color of the restoration to achieve a high degree of consistency in color with the surrounding natural teeth, a natural and realistic effect is realized. On this basis, a restoration is coated to ensure that the color remains bright and natural for a long time, thereby better meeting the clinical requirements for aesthetics.

[0004] Currently, when existing transparent glazes are used for upper tooth restoration, it is difficult to perfectly match the optical properties of natural teeth, resulting in the whitening of the restored upper teeth and affecting aesthetics. In the preparation process of some transparent glazes, insufficient consideration is given to the synergistic effect of each component, resulting in poor optical uniformity of the enamel layer. When light propagates in it, abnormal scattering and absorption occur, and the clear and bright effect of natural teeth cannot be presented, making it difficult to meet the needs of patients for oral aesthetic restoration.

[0005] For example, CN114455953A discloses a porcelain powder for all-ceramic dentures with a core-shell structure. This solution uses nanocrystalline leucite crystals as the core and basic glass powder as the shell, enabling the nanocrystalline leucite crystals to be evenly distributed in the basic glass powder, thereby obtaining a porcelain powder with uniform properties, matching the zirconia crown bottom, and high strength. However, this core-shell structure significantly reduces the transparency of the glaze layer, limiting the application fields of the material.

[0006] In the dental ceramic paste preparation method disclosed in CN111467246A, a specific amount of hydrophobized SiO2 is introduced. The purpose is to maintain the long-term stability of the glaze paste and endow it with excellent coating feel. However, hydrophobized SiO2 has the characteristic of a relatively high melting point. When it is fully mixed with the glaze paste and coated on the surface of the restoration, after the calcination process, the glaze surface often turns white. This whitening condition will have an adverse impact on the aesthetics of the glaze surface to a great extent, making it difficult for the restoration to achieve an ideal appearance effect and unable to fully meet the strict requirements for aesthetics in dental restoration.

[0007] Therefore, there is a need to develop dental restoration materials with a clear and bright effect, high dental aesthetics, and excellent texture. Summary of the Invention

[0008] Aiming at the deficiencies of the prior art, the purpose of the present invention is to provide an enamel composition, enamel surface, and application. By using specific inorganic additives, the uniform stability of the enamel composition can be significantly improved, and the absolute value of the difference between the refractive index of the glass powder and the refractive index of the dispersion composition is controlled within 0.1, which can reduce the refraction and scattering of light at the interface after the two are mixed, so that the enamel surface has a clear and bright effect, and an enamel structure with uniform components and excellent optical properties is obtained.

[0009] To achieve this purpose, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides an enamel composition, which includes glass powder and a dispersion composition; the dispersion composition includes an organic liquid and an inorganic additive; wherein, the absolute value of the difference between the refractive index of the glass powder and the refractive index of the dispersion composition is within 0.1; the organic liquid includes a combination of an alcohol solvent and an ester solvent; the inorganic additive includes clay minerals and / or diatomaceous earth.

[0011] The present invention has found through research that for the enamel surface to have a clear and bright effect, the key points are twofold. First, the components of the enamel composition are uniform and stable, so that after calcination, the unclear situation caused by uneven composition will not occur. Second, the refractive indices of the glass powder and the organic liquid in the enamel composition should be close. For the first point, the present invention creatively discovers that adding clay minerals and / or diatomaceous earth to the enamel composition can improve the dispersion uniformity of the glass powder in the organic liquid, thereby enhancing the uniform stability of the enamel composition.

[0012] Generally speaking, according to optical theory, changes in the transparency of a liquid will cause corresponding changes in its internal microstructure and molecular arrangement state, thereby affecting the propagation rate of light in the liquid and achieving precise adjustment of the refractive index of the liquid. In order to make the light propagation smoother, improve the transparency of the liquid in visible light, and ensure that the enamel coated on the denture is clear and transparent, it is necessary to gradually approximate the refractive index of the liquid to the refractive index of the powder to ensure that the refraction and scattering of light at the interface after the two are mixed will be significantly reduced.

[0013] However, in the research of the present invention, it is found that inorganic additives such as clay minerals and / or diatomaceous earth are difficult to dissolve in the combined organic liquid of alcohol solvents and ester solvents. Generally, the additives used in the art need to be dissolved in the organic liquid. Since the amount of the additive is small, after it is dissolved in the organic liquid, the additive can be fully dissolved and dispersed in the organic liquid, so the influence on the refractive index of the organic liquid is relatively low. Generally, the refractive index of the organic liquid is adjusted directly by calculating with the liquid-phase refractive index formula, and the refractive index of the organic liquid is controlled to be close to that of the glass powder to solve the problem of the refractive index difference. However, the clay minerals and / or diatomaceous earth used in the present invention are difficult to be fully dissolved in the organic liquid, and even a small amount of inorganic additive will cause changes and inhomogeneity in the refractive index inside the dispersion composition.

[0014] To solve the above problems, the present invention makes the following two aspects of adjustments. On the one hand, by adding an ester solvent to the organic liquid, the transparency of the organic liquid can be adjusted, thereby further adjusting the refractive index of the organic liquid. On the other hand, after the inorganic additive is fully dispersed in the organic liquid, the refractive index of the dispersion composition is made close to that of the glass powder. Through the above scheme, the clear glaze prepared by the present invention can present a more transparent and clear texture closer to natural teeth, fully meeting the urgent needs of the oral restoration field for high-transparency enamel materials, and effectively improving the aesthetic effect and overall quality of oral restoration. The present invention can ensure that the paste is uniform and stable, and in the subsequent mixing and molding process, a uniform and excellent optical performance enamel structure can be constructed.

[0015] In the present invention, the absolute value of the difference between the refractive index of the glass powder and the refractive index of the organic liquid is within 0.1, for example, it can be 0.1, 0.09, 0.08, 0.07, 0.06, 0.05, 0.04, 0.03, 0.02, 0.01, 0.009, 0.008, 0.007, 0.006, 0.005, 0.004, 0.003, 0.002, 0.001 or 0, etc.

[0016] Preferably, the mass ratio of the alcohol solvent to the ester solvent is (33 - 45):(0.2 - 5.1). The mass fraction of the alcohol solvent can be, for example, 33, 33.4, 33.7, 34, 34.3, 34.6, 34.9, 35.2, 35.5, 35.8, 36, 38, 39, 40, 41, 42 or 45, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable; the mass fraction of the ester solvent can be, for example, 0.2, 0.8, 1.3, 1.9, 2.4, 3, 3.5, 4.1, 4.6 or 5.1, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0017] Through extensive research, the present invention has found that when the mass ratio of the alcohol solvent to the ester solvent is within the above range, the refractive index of the resulting dispersion composition can better match that of the glass powder, thereby better enhancing the clear and bright effect.

[0018] Preferably, the alcohol solvent includes monohydric alcohol and / or polyhydric alcohol, preferably dihydric alcohol.

[0019] Preferably, the monohydric alcohol includes any one or a combination of at least two of hexanol, 2-ethyl-1-hexanol, octanol, benzyl alcohol, lauryl alcohol, furfuryl alcohol, or n-heptanol. Typical but non-limiting combinations include the combination of hexanol and 2-ethyl-1-hexanol, the combination of octanol and 2-ethyl-1-hexanol, the combination of hexanol and octanol, the combination of benzyl alcohol and 2-ethyl-1-hexanol, the combination of hexanol and benzyl alcohol, the combination of lauryl alcohol and furfuryl alcohol, the combination of furfuryl alcohol and 2-ethyl-1-hexanol, the combination of n-heptanol and 2-ethyl-1-hexanol, the combination of lauryl alcohol and n-heptanol, and the combination of n-heptanol and octanol.

[0020] Preferably, the polyhydric alcohol includes any one or a combination of at least two of 1,3-butanediol, 1,2-propanediol, cyclohexanol, glycerol, diethylene glycol, triethylene glycol, or terpineol. Typical but non-limiting combinations include the combination of 1,3-butanediol and 1,2-propanediol, the combination of cyclohexanol and 1,2-propanediol, the combination of 1,3-butanediol and cyclohexanol, the combination of glycerol and 1,2-propanediol, the combination of 1,3-butanediol and glycerol, the combination of triethylene glycol and 1,2-propanediol, the combination of terpineol and 1,2-propanediol, and the combination of diethylene glycol and terpineol.

[0021] Preferably, the ester solvent includes any one or a combination of at least two of ethyl acetate, dimethyl terephthalate, dimethyl phthalate, or triethyl citrate. Typical but non-limiting combinations include the combination of ethyl acetate and dimethyl terephthalate, the combination of dimethyl phthalate and dimethyl terephthalate, the combination of ethyl acetate and dimethyl phthalate, the combination of triethyl citrate and dimethyl terephthalate, and the combination of ethyl acetate and triethyl citrate.

[0022] Preferably, the refractive index of the organic liquid is 1.435 to 1.486. For example, it can be 1.435, 1.441, 1.447, 1.452, 1.458, 1.464, 1.469, 1.475, 1.481, or 1.486, etc., but is not limited to the listed values. Other unlisted values within this range are equally applicable.

[0023] Preferably, by mass percentage, the glass powder includes: SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, ZnO, and alkaline earth metals.

[0024] The present invention further preferably has the glass powder component as the above composition, which can better match the refractive index of the dispersion composition to improve the aesthetics and texture of the restored teeth.

[0025] Preferably, by mass percentage, the glass powder includes: 57.2 - 66.5 wt% of SiO2, 8.1 - 12.2 wt% of Al2O3, 1.0 - 3.2 wt% of Li2O, 3.7 - 7.5 wt% of Na2O, 1.0 - 3.2 wt% of K2O, 4.4 - 10.1 wt% of B2O3, 1.0 - 2.8 wt% of ZnO, and 0.5 - 1.6 wt% of alkaline earth metals.

[0026] Among them, the mass content of SiO2 in the glass powder is 57.2 - 66.5 wt%, for example, it can be 57.2 wt%, 58.3 wt%, 59.3 wt%, 60.3 wt%, 61.4 wt%, 62.4 wt%, 63.4 wt%, 64.5 wt%, 65.5 wt% or 66.5 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0027] The mass content of Al2O3 in the glass powder is 8.1 - 12.2 wt%, for example, it can be 8.1 wt%, 8.6 wt%, 9.1 wt%, 9.5 wt%, 10 wt%, 10.4 wt%, 10.9 wt%, 11.3 wt%, 11.8 wt% or 12.2 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0028] The mass content of Li2O in the glass powder is 1.0 - 3.2 wt%, for example, it can be 6.8 wt%, 7.3 wt%, 7.7 wt%, 8.1 wt%, 8.5 wt%, 8.9 wt%, 9.3 wt%, 9.7 wt%, 10.1 wt% or 10.5 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0029] The mass content of Na2O in the glass powder is 3.7 - 7.5 wt%, for example, it can be 3.7 wt%, 4.2 wt%, 4.6 wt%, 5 wt%, 5.4 wt%, 5.9 wt%, 6.3 wt%, 6.7 wt%, 7.1 wt% or 7.5 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0030] The mass content of K2O in the glass powder is 1.0 - 3.2 wt%, for example, it can be 6.8 wt%, 7.3 wt%, 7.7 wt%, 8.1 wt%, 8.5 wt%, 8.9 wt%, 9.3 wt%, 9.7 wt%, 10.1 wt% or 10.5 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0031] The mass content of B2O3 in the glass powder is 4.4 - 10.1 wt%, for example, it can be 4.4 wt%, 5.1 wt%, 5.7 wt%, 6.3 wt%, 7 wt%, 7.6 wt%, 8.2 wt%, 8.9 wt%, 9.5 wt% or 10.1 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0032] The mass content of ZnO in the glass powder is 1.0 - 2.8 wt%, for example, it can be 1.0 wt%, 1.2 wt%, 1.4 wt%, 1.6 wt%, 1.8 wt%, 2 wt%, 2.2 wt%, 2.4 wt%, 2.6 wt% or 2.8 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0033] The present invention further preferably controls the mass content of ZnO within the above range, which has the effect of improving the transparency of the glaze surface.

[0034] The mass content of alkaline earth metals in the glass powder is 0.5 - 1.6 wt%, for example, it can be 0.5 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt% or 1.6 wt% etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0035] Preferably, the alkaline earth metals include magnesium oxide and / or calcium oxide.

[0036] In the present invention, the alkaline earth metals preferably contain both magnesium oxide and calcium oxide at the same time, which helps to improve the flatness and smoothness of the glaze surface, thereby improving the gloss of the glaze surface.

[0037] Preferably, when the alkaline earth metals include both magnesium oxide and calcium oxide at the same time, the mass ratio of calcium oxide to magnesium oxide is (2 - 6):1, for example, it can be 2:1, 2.5:1, 3:1, 3.5:1, 4:1, 4.5:1, 5:1, 5.5:1 or 6:1 etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0038] Preferably, the glass powder includes rare earth metal oxides.

[0039] Preferably, the rare earth metal oxide includes CeO2.

[0040] The present invention preferably adds CeO2, which can ensure the smooth and flat glaze surface and reduce pinholes and bubbles.

[0041] Preferably, based on the mass percentage, the content of the rare earth metal oxide in the glass powder is 0.1 - 0.3 wt%, for example, it can be 0.1 wt%, 0.13 wt%, 0.15 wt%, 0.17 wt%, 0.19 wt%, 0.22 wt%, 0.24 wt%, 0.26 wt%, 0.28 wt% or 0.3 wt%, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0042] Preferably, the refractive index of the glass powder is 1.421 - 1.503, for example, it can be 1.421, 1.431, 1.44, 1.449, 1.458, 1.467, 1.476, 1.485, 1.494 or 1.503, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0043] Preferably, the D50 particle size of the glass powder is 5 - 15 μm, for example, it can be 5 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0044] Preferably, based on the mass percentage, the dental enamel composition includes 45 - 65 wt% of glass powder and 34.95 - 54.95 wt% of organic liquid.

[0045] Among them, the mass fraction of the glass powder in the dental enamel composition is 45 - 65 wt%, for example, it can be 45 wt%, 48 wt%, 50 wt%, 52 wt%, 54 wt%, 57 wt%, 59 wt%, 61 wt%, 63 wt% or 65 wt%, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0046] The mass fraction of the organic liquid in the dental enamel composition is 34.95 - 54.95 wt%, for example, it can be 34.95 wt%, 37.18 wt%, 39.4 wt%, 41.62 wt%, 43.84 wt%, 46.07 wt%, 48.29 wt%, 50.51 wt%, 52.73 wt% or 54.95 wt%, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0047] Preferably, the mass content of the inorganic auxiliary in the enamel surface composition is 0.05-2 wt%, for example, it can be 0.05 wt%, 0.27 wt%, 0.49 wt%, 0.7 wt%, 0.92 wt%, 1.14 wt%, 1.35 wt%, 1.57 wt%, 1.79 wt% or 2 wt%, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0048] Preferably, the clay mineral includes any one or a combination of at least two of lithium montmorillonite clay, montmorillonite, sodium-based bentonite, magnesium aluminum silicate or attapulgite clay. Among them, typical but non-limiting combinations are the combination of lithium montmorillonite clay and montmorillonite, the combination of sodium-based bentonite and montmorillonite, the combination of magnesium aluminum silicate and montmorillonite, the combination of lithium montmorillonite clay and magnesium aluminum silicate, the combination of attapulgite clay and montmorillonite, and the combination of lithium montmorillonite clay and attapulgite clay.

[0049] In the present invention, it is preferred to select the above substances as the inorganic auxiliary, which has a better dispersion effect.

[0050] Preferably, the lithium montmorillonite clay includes Lithium montmorillonite clay.

[0051] Preferably, when the inorganic auxiliary includes a clay mineral and diatomite, the mass ratio of the clay mineral to diatomite is 0.8-1:1. For example, it can be 0.8:1, 0.82:1, 0.83:1, 0.84:1, 0.85:1, 0.86:1, 0.90:1, 0.92:1, 0.93:1, 0.95:1, 0.96:1, 0.98:1 or 1:1, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0052] In the present invention, it is preferred to adopt the combination of the clay mineral and diatomite and control the mass ratio of the two within the above range, so as to better interact with the glass powder and improve the dispersion uniformity and stability of the paste.

[0053] Preferably, the powder particle size D50 of the inorganic auxiliary is 0.1-5 μm. For example, it can be 0.1 μm, 0.2 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5 μm, etc., but not limited to the listed values, and other unlisted values within this range are equally applicable.

[0054] It should be noted that the present invention has no special requirements for the preparation process of the above-mentioned glass powder, and it can be prepared by using the preparation methods of glass powder well-known to those skilled in the art. For example: the preparation method of glass powder includes: calculating the input amount of raw materials according to the percentage of oxides, melting the weighed raw materials at high temperature, and then water quenching to obtain glass slag, and preparing the water quenched slag into the required particle size by a vibration crusher.

[0055] Preferably, the refractive index of the dispersion composition is 1.454 to 1.502, and for example, it can be 1.454, 1.46, 1.465, 1.47, 1.476, 1.481, 1.486, 1.492, 1.497 or 1.502, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0056] In a second aspect, the present invention provides an enamel surface, which is obtained by calcining the enamel surface composition described in the first aspect.

[0057] Preferably, the preparation method of the enamel surface includes: mixing glass powder, inorganic additives, alcohol solvents and ester solvents, and performing calcination to obtain the enamel surface composition.

[0058] The present invention has no special restrictions on the above mixing steps and processes, and the steps and processes well-known to those skilled in the art can be adopted, as long as the mixing is uniform.

[0059] Preferably, the calcination temperature is not lower than 730 °C, and for example, it can be 730 °C, 740 °C, 750 °C, 760 °C, 770 °C, 780 °C, 790 °C, 800 °C, 810 °C, 820 °C, 830 °C, 840 °C, 850 °C, 860 °C, 870 °C, 880 °C, 890 °C or 900 °C, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0060] Preferably, the heat preservation time of the calcination is 1 to 2 minutes, and for example, it can be 1 minute, 1.2 minutes, 1.3 minutes, 1.4 minutes, 1.5 minutes, 1.6 minutes, 1.7 minutes, 1.8 minutes, 1.9 minutes or 2 minutes, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0061] Preferably, the transparency of the enamel surface is 55 to 65%, and for example, it can be 55%, 57%, 58%, 59%, 60%, 61%, 62%, 63%, 64% or 65%, etc., but is not limited to the listed values, and other unlisted values within this range are equally applicable.

[0062] In a third aspect, the present invention provides an enamel composition as described in the first aspect, and / or the use of the enamel surface as described in the second aspect in dental restoration.

[0063] Preferably, the enamel composition is applied in a metal dental restoration material, a feldspathic glass dental restoration material, or a ceramic dental restoration material.

[0064] Preferably, the ceramic dental restoration material includes any one or at least two combinations of lithium disilicate glass-ceramic, leucite-reinforced feldspathic porcelain, glass-infiltrated ceramic, zirconia ceramic, or alumina ceramic. Typical but non-limiting combinations include the combination of lithium disilicate glass-ceramic and leucite-reinforced feldspathic porcelain, the combination of glass-infiltrated ceramic and leucite-reinforced feldspathic porcelain, the combination of lithium disilicate glass-ceramic and glass-infiltrated ceramic, the combination of zirconia ceramic and leucite-reinforced feldspathic porcelain, the combination of lithium disilicate glass-ceramic and zirconia ceramic, and the combination of alumina ceramic and zirconia ceramic.

[0065] Compared with the prior art, the present invention has at least the following beneficial effects:

[0066] (1) By selecting specific inorganic additives, the enamel composition provided by the present invention can significantly improve the uniform stability of the paste, thereby improving the transparency of the final enamel surface.

[0067] (2) By controlling the absolute value of the difference between the refractive indices of the dispersion composition and the glass powder within 0.1, the light propagates more smoothly in the enamel composition, improving the transparency of the liquid in visible light, ensuring that the enamel surface finally applied to the denture is clear and transparent, and the transparency of the final enamel surface is between 47% and 65%, preferably between 60% and 65%; and the uniform stability test shows no obvious stratification after 1 day of placement, and no stratification after 15 days of placement under preferred conditions.

[0068] (3) The enamel surface provided by the present invention can present a transparent and clear texture closer to natural teeth, fully meeting the urgent need for high-transparency enamel materials in the field of oral restoration, and effectively improving the aesthetic effect and overall quality of oral restoration. BRIEF DESCRIPTION OF THE DRAWINGS

[0069] Figure 1 is a finished product diagram of the enamel composition obtained in Example 10 after being applied to the upper teeth.

[0070] Figure 2 is a finished product diagram of the enamel composition obtained in Example 15 after being applied to the upper teeth.

[0071] Figure 3 is a finished product diagram of the enamel composition obtained in Example 19 after being applied to the upper teeth.

[0072] Figure 4 This is the finished product picture after applying the dental enamel composition obtained in Example 20 on the upper teeth. Detailed implementation manners

[0073] For ease of understanding the present invention, the following examples are listed. Those skilled in the art should understand that the said examples are only for helping to understand the present invention and should not be regarded as specific limitations on the present invention.

[0074] Term explanation:

[0075] Dental enamel composition: It is a uniformly mixed solid-liquid mixture.

[0076] Dental enamel: It is a solid-phase product obtained after calcining the dental enamel composition.

[0077] Refractive index: It refers to the ratio of the propagation speed of a light beam in a vacuum to that in the substance to be measured.

[0078] Layering: In the present invention, layering means that obvious boundaries appear between the powder and the liquid in the glaze paste.

[0079] During the use of transparent glaze, the glaze paste often presents a milky white or opaque state due to the refractive index mismatch between the powder phase and the liquid phase. In addition, the agglomeration phenomenon and uneven dispersion of the powder particles further aggravate the light scattering, resulting in a significant increase in the whiteness of the glaze paste. This milky white state before firing affects the appearance quality of the glaze, making it impossible to achieve a perfect color match between the restoration and the surrounding teeth. It is difficult for restorers to make accurate judgments based on established color standards and visual experience, resulting in color judgment errors when applying the upper teeth. In addition, if the paste does not have a stable system, when powder sedimentation occurs, the uniformity inside the paste is damaged, and the originally uniformly distributed powder accumulates at the bottom, forming a concentration gradient. When light passes through this non-uniform paste, strong scattering and refraction will occur in the powder aggregation area, and it cannot penetrate smoothly, thus greatly reducing the transparency of the glaze paste and making it unable to present a clear and bright effect, which can also affect the beauty and texture of the teeth. Therefore, optimizing the refractive index matching of the powder and the liquid phase and improving the powder dispersion state are the keys to solving this problem.

[0080] In this regard, the specific solutions of the present invention will be described in detail through the following specific implementation manners.

[0081] Glass powder G-1: The particle size D50 of the glass powder G-1 is 8 μm. Calculated based on the total mass percentage being 100, the glass powder G-1 includes the following components:

[0082]

[0083]

[0084] The preparation method of glass powder G1 includes: mixing raw materials according to the mass percentages of the above-mentioned oxides, melting the mixed raw materials at a high temperature of 1200 °C, then quenching with water to obtain glass slag, and preparing the water-quenched slag into the required particle size by a vibration crusher, where the particle size D50 of the glass powder is 8 μm.

[0085] Glass powder G2: The particle size D50 of glass powder G2 is 5 μm. Based on the total mass percentage being 100, glass powder G2 includes the following components:

[0086]

[0087] The preparation method of glass powder G2 includes: mixing raw materials according to the mass percentages of the above-mentioned oxides, melting the mixed raw materials at a high temperature of 1180 °C, then quenching with water to obtain glass slag, and preparing the water-quenched slag into the required particle size by a vibration crusher, where the particle size D50 of the glass powder is 5 μm.

[0088] Glass powder G3: The particle size D50 of glass powder G3 is 10 μm. Based on the total mass percentage being 100, glass powder G3 includes the following components:

[0089]

[0090] The preparation method of glass powder G3 includes: mixing raw materials according to the mass percentages of the above-mentioned oxides, melting the mixed raw materials at a high temperature of 1250 °C, then quenching with water to obtain glass slag, and preparing the water-quenched slag into the required particle size by a vibration crusher, where the particle size D50 of the glass powder is 10 μm.

[0091] Glass powder G4: The particle size D50 of glass powder G4 is 15 μm. Based on the total mass percentage being 100, glass powder G4 includes the following components:

[0092]

[0093]

[0094] The preparation method of glass powder G4 includes: mixing raw materials according to the mass percentages of the above-mentioned oxides, melting the mixed raw materials at a high temperature of 1230 °C, then quenching with water to obtain glass slag, and preparing the water-quenched slag into the required particle size by a vibration crusher, where the particle size D50 of the glass powder is 15 μm.

[0095] Glass powder G5: Glass powder G5 is the same as glass powder G3 in all respects except that CeO2 is replaced by Y2O3.

[0096] Glass powder G6: Except that the content of ZnO is replaced by 3.5 wt% and the content of SiO2 is adjusted to 58.9 wt% accordingly, the rest is the same as glass powder G3.

[0097] Glass powder G7: Except that only MgO is contained in the alkaline earth metals, the rest is the same as glass powder G3.

[0098] Examples 1 to 15

[0099] This example provides an enamel composition. Based on a total mass percentage of 100, the composition of the enamel composition is shown in Table 1.

[0100] Table 1

[0101]

[0102]

[0103] Examples 19 to 21

[0104] Examples 19 to 21 provide an enamel composition. Except that glass powders G5 to G7 are used respectively, the rest is the same as Example 10 and will not be elaborated here.

[0105] Testing of the refractive index of glass powder and organic liquid

[0106] ① Testing of the refractive index of glass powder: Put the glass powder into a high-temperature muffle furnace, melt it at 1300 °C for 1 h, then pour it into a mold and let it stand and cool. After obtaining a cuboid sample block with a thickness of about 20 * 20 * 15 mm, polish the two testing surfaces with 800, 1000, 1500, and 2000-mesh sandpapers respectively to obtain a bright surface. Then use an Abbe refractometer for testing. Wipe the prism surface clean and test three times, and take the average value as the final refractive index.

[0107] ② Testing of the refractive index of liquid: Wipe the prism surface clean, drop two drops of liquid onto the prism surface, close the prism group. When the bright-dark dividing line coincides exactly with the crosshair in the eyepiece, the corresponding value is the refractive index. Test three times and take the average value as the final refractive index.

[0108] The refractive index data of the glass powder and the organic liquid in the above examples and comparative examples are shown in Table 2.

[0109] Table 2

[0110]

[0111]

[0112] The test method for tooth enamel composition is as follows:

[0113] 1. Measurement of transmittance of tooth enamel composition

[0114] The enamel composition was dried for 35 minutes. 5 g of the resulting solid phase was pressed and then fired. The firing temperature was set at 400°C, the heating rate was 15°C / minute, and the vacuum level was 91-98 kPa. When the maximum firing temperature of 680°C was reached, the temperature was maintained for 50 minutes. The composition was then cooled to room temperature and polished using 1000-, 1500-, and 2000-grit sandpaper. Samples with a length and width of 20 mm and a thickness of 1 mm were prepared. Transparency was measured using an HZ-V3 high-precision haze meter.

[0115] 2. Color and state test after calcination

[0116] The enamel composition was adjusted to a suitable consistency and applied on a 15 mm diameter zirconium oxide disc of the same color. The mixture was then dried at 400°C for 2 minutes, heated to 730°C at a rate of 55°C / min, and kept at that temperature for 2 minutes. The calcination curve test was performed to observe the surface state after calcination.

[0117] 3. Test on uniformity and stability of tooth enamel composition

[0118] The tooth enamel composition was fully stirred, and 3 g of the composition was placed in each container. The composition was observed after 1 day, 3 days, 7 days, and 15 days to see whether there was obvious stratification between the powder and the liquid.

[0119] The test results of the above embodiments and comparative examples are shown in Table 3.

[0120] Table 3

[0121]

[0122] In Table 3, the stratification phenomenon is ranked from light to heavy according to the severity of stratification: no stratification, no obvious stratification, signs of stratification, slight stratification, obvious stratification, aggravated stratification, severe stratification and solid-liquid separation; the transparency of the calcined state is ranked from the most transparent to the gradually decreasing transparency: high transparency, good transparency, fair transparency, average transparency, poor transparency and poor transparency.

[0123] From Tables 1 to 3, we can see the following points:

[0124] (1) From the comprehensive implementation examples 1 to 21, it can be seen that the enamel surface composition provided by the present invention has excellent uniform stability. There is no obvious stratification after standing for one day, and only signs of stratification or slight stratification appear after standing for 3 days. Moreover, its transparency can achieve an effect above average. Further preferably, in implementation examples 10, 13 to 14, not only does the enamel surface composition not stratify after standing for 15 days, but also it has high transparency or good transparency, with an obvious clear feeling, and the transmittance is above 60%;

[0125] (2) From the comprehensive implementation examples 3 and comparative examples 1 to 3, it can be seen that in the case of the same other components, in comparative example 1, only 1,3 - butanediol is used as the organic liquid, and in comparative examples 2 and 3, butanediol, dimethyl ether, and glucose are respectively combined with 1,3 - butanediol as the organic liquid, resulting in a large difference in the refractive index of the composition after mixing with the inorganic auxiliary agent and the refractive index of the glass powder. And after many adjustments by researchers, it is also difficult to obtain refractive index data closer to that of the glass powder, indicating that the combination of alcohol and ester adopted by the present invention can better cooperate with the inorganic auxiliary agent to obtain a composition with a refractive index closer to that of the glass powder, and finally the obtained product has better transparency; moreover, the glass composition in comparative examples 1 to 3 stratifies severely, indicating that the ester solvent can also cooperate with the inorganic auxiliary agent to achieve a better dispersion effect.

[0126] From the comprehensive implementation examples 3 and comparative examples 4 to 6, it can be seen that the inorganic auxiliary agent selected in the present invention is clay mineral and / or diatomaceous earth, which can not only improve the uniform stability but also improve the transparency of the product.

[0127] Combined with comparative examples 1 to 6, it can be seen that the present invention needs to combine the specific inorganic auxiliary agent and organic liquid in the present invention, and the two work synergistically to simultaneously obtain an enamel surface composition with high transparency and excellent uniform stability.

[0128] (3) From the comprehensive implementation examples 10 and 17 to 18, it can be seen that the present invention further preferably uses the combination of montmorillonite and diatomaceous earth as the inorganic auxiliary agent, which can further improve the dispersion uniform stability of the slurry and at the same time improve the transparency of the enamel surface.

[0129] (4) It can be seen from a comprehensive comparison of Example 10 with Examples 15 to 16 that the content of the inorganic auxiliary in Example 10 is 3.5 wt%, compared with the contents of the inorganic auxiliary in Examples 15 to 16 being 4.0 wt% and 0.01 wt% respectively. In Example 10, the transparency of the tooth enamel surface is high, the clear sense is more obvious, and there is no delamination after 15 days of placement. In Examples 15 to 16, not only is the transparency decreased compared with Example 10, but also slight delamination occurs in Example 16 after 1 day of placement, and delamination signs appear in Example 15 after 15 days of placement. The dispersion uniformity and stability are decreased compared with Example 1. Thus, it is shown that the present invention preferably controls the content of the inorganic auxiliary within a reasonable range, which can further improve the transparency and uniform stability. The finished product diagrams of the tooth enamel compositions obtained in Example 10 and Example 15 after being applied to the teeth are respectively as Figures 1 - 2 shown, and by comparing Figure 1 and Figure 2 it can be seen that the finished product obtained in Example 10 is clearer, more transparent and brighter.

[0130] (5) It can be seen from a comprehensive comparison of Example 10 with Examples 19 to 21 that in Example 10, the glass powder G3 with a specific composition is used. Compared with replacing CeO2 with Y2O3 in Example 19, the content of ZnO being on the high side in Example 20, and only containing MgO as the alkaline earth metal in Example 21, in Example 10, the refractive index of the glass powder is relatively close to the refractive index of the dispersion composition. Also, in Example 10, the transparency of the tooth enamel surface is high, the clear sense is more obvious, and there is no delamination after 15 days of placement. In Examples 19 to 21, the refractive index of the glass powder is relatively far from the refractive index of the dispersion composition. The transparency of the finally obtained tooth enamel composition is average, and there are delamination signs after 3 days of placement, and serious delamination occurs after 15 days of placement. Thus, it is shown that the present invention preferably uses a glass powder with a suitable composition, which can further improve the uniform stability and transparency of the tooth enamel composition. The diagrams presented after applying the tooth enamel compositions in Example 10, Example 19, and Example 20 to the teeth are respectively as Figure 1 、 Figures 3 - 4 shown. From Figure 1 、 Figures 3 - 4 it can be seen that the restored teeth obtained in Example 10 are clear, transparent and bright, and are significantly more beautiful than the restored teeth in Example 19 and Example 20.

[0131] The present invention uses the above-mentioned examples to illustrate the detailed features of the present invention, but the present invention is not limited to the above detailed features, that is, it does not mean that the present invention must rely on the above detailed features to be implemented. Those skilled in the art should understand that any improvement to the present invention, the equivalent replacement of the technical features selected by the present invention, and the addition of auxiliary technical features, the selection of specific methods, etc., all fall within the protection scope and the disclosure scope of the present invention.

Claims

1. A dental enamel composition, characterized in that, The enamel surface composition comprises a glass powder and a dispersion composition; The dispersion composition comprises an organic liquid and an inorganic auxiliary; Wherein, the absolute value of the difference between the refractive index of the glass powder and the refractive index of the dispersion composition is within 0.1; The organic liquid comprises a combination of an alcohol solvent and an ester solvent; The inorganic auxiliary comprises a clay mineral and / or diatomaceous earth.

2. The enamel surface composition according to claim 1, characterized in that, The mass ratio of the alcohol solvent to the ester solvent is (33-45):(0.2-5.1); Preferably, the alcohol solvent comprises a monohydric alcohol and / or a polyhydric alcohol, preferably a dihydric alcohol; Preferably, the monohydric alcohol comprises any one or a combination of at least two of hexanol, 2-ethyl-1-hexanol, octanol, benzyl alcohol, lauryl alcohol, furfuryl alcohol or n-heptanol; Preferably, the polyhydric alcohol comprises any one or a combination of at least two of 1,3-butanediol, 1,2-propanediol, cyclohexanol, glycerol, diethylene glycol, triethylene glycol or terpineol; Preferably, the ester solvent comprises any one or a combination of at least two of ethyl acetate, dimethyl terephthalate, dimethyl phthalate or triethyl citrate; Preferably, the refractive index of the organic liquid is 1.435-1.

486.

3. The enamel surface composition according to claim 1 or 2, characterized in that, By mass percentage, the glass powder comprises: SiO2, Al2O3, Li2O, Na2O, K2O, B2O3, ZnO and alkaline earth metals; Preferably, by mass percentage, the glass powder comprises: 57.2-66.5 wt% of SiO2, 8.1-12.2 wt% of Al2O3, 1.0-3.2 wt% of Li2O, 3.7-7.5 wt% of Na2O, 6.8-10.5 wt% of K2O, 4.4-10.1 wt% of B2O3, 1.0-2.8 wt% of ZnO and 0.5-1.6 wt% of alkaline earth metals; Preferably, the alkaline earth metal comprises magnesium oxide and / or calcium oxide; Preferably, when the alkaline earth metal comprises both magnesium oxide and calcium oxide, the mass ratio of calcium oxide to magnesium oxide is 2-6:

1.

4. The enamel surface composition according to any one of claims 1 to 3, characterized in that, The glass powder comprises rare earth metal oxides; Preferably, the rare earth metal oxide comprises CeO2; Preferably, by mass percentage, the content of the rare earth metal oxide in the glass powder is 0.1-0.3 wt%.

5. The enamel surface composition according to any one of claims 1 to 4, characterized in that, The refractive index of the glass powder is 1.421-1.503; Preferably, the particle size D50 of the glass powder is 5-15 μm.

6. The enamel surface composition according to any one of claims 1 to 5, characterized in that By mass percentage, the enamel surface composition comprises 45-65 wt% of glass powder and 34.95-54.95 wt% of organic liquid.

7. The enamel surface composition according to any one of claims 1 to 6, characterized in that The mass content of the inorganic auxiliary in the enamel surface composition is 0.05-3.5 wt%; Preferably, the clay mineral comprises any one or a combination of at least two of lithium montmorillonite clay, montmorillonite, sodium-based bentonite, magnesium aluminum silicate or attapulgite clay; Preferably, when the inorganic auxiliary comprises a clay mineral and diatomaceous earth, the mass ratio of the clay mineral to the diatomaceous earth is 0.8-1:1; Preferably, the powder particle size D50 of the inorganic auxiliary is 0.1-5 μm; Preferably, the refractive index of the dispersion composition is 1.454 to 1.

502.

8. An enamel surface, characterized in that, The dental enamel surface is obtained by calcining the dental enamel surface composition according to any one of claims 1 to 7.

9. The enamel surface according to claim 8, characterized in that, The temperature of the calcination is not lower than 730 °C; Preferably, the heat preservation time of the calcination is 1 to 2 minutes.

10. Use of the dental enamel surface composition according to any one of claims 1 to 7, and / or the dental enamel surface according to claim 8 or 9 in dental restoration; Preferably, the dental enamel surface composition or the dental enamel surface is used in metallic dental restoration materials, feldspathic glass dental restoration materials or ceramic dental restoration materials.

Citation Information

Patent Citations

  • Dental porcelain paste

    CN111467246A